The role of astaxanthin‐Cu2+ in stabilizing glycated human serum albumin for type 2 diabetes mellitus management: a computational approach - Abiyyu, Naufal; Fitrianita, Alfia; Artika, I Made; Siregar, Josephine Elizabeth; Wibowo, Syahputra; Wardhani, Bantari Wisynu Kusuma; Budi, Canggih Setya; Nuringtyas, Tri Rini (Universitas Gadjah Mada, 2026)
Type 2 diabetes mellitus (T2DM) leads to the non‐enzymatic glycation of proteins, resulting in the formation of advanced glycation end products (AGEs), which contribute to diabetic complications. Human serum albumin (HSA), a major plasma protein, undergoes structural alterations upon glycation (gHSA), reducing its stability and biological functions. Astaxanthin (ASX), a potent antioxidant, is limited by its instability and moderate binding affinity. In this study, we explore the use of copper (Cu2+) to form a stable ASX‐Cu2+ complex, enhancing the antioxidant properties of ASX and improving its interaction with HSA and gHSA. Utilizing computational approaches such as molecular docking, molecular dynamics (MD) simulations, and free energy landscape (FEL) mapping, we analyze the stability and conformational changes of HSA and gHSA upon binding with ASX and ASX‐Cu2+. The residue interaction network (RIN) analysis reveals that ASX‐Cu2+ complexes create a more robust and interconnected network of non‐covalent interactions, particularly enhancing hydrogen bonding, π‐stacking, and ionic interactions. The ASX‐Cu2+ complex at a 1:2 molar ratio significantly improved the binding affinity and structural stability of both native and glycated HSA, reducing protein fluctuations and promoting a more compact conformation. These findings suggest that ASX‐Cu2+ complexes offer therapeutic potential for stabilizing albumin under glycation‐induced stress, with implications for managing oxidative stress and diabetes‐related complications.